Numerical research on combustion and emissions behaviors of a medium compression ratio direct-injection twin-spark plug synchronous ignition methanol engine under steady-state lean-burn conditions. (15th January 2021) - Gong, Changming; Sun, Jingzhen; Liu, Fenghua
Abstract: Twin-spark plug synchronous ignition is an effective means of improving the stability of combustion and extending the lean-burn limit of the spark ignition engine. In this study, the distribution of mixture concentration, combustion, and emissions-related behaviors of a direct-injection twin-spark plug synchronous ignition methanol engine are numerically investigated to assess its lean-burn performance and solve for stable combustion under a medium compression ratio. The simulation results shows that the timing of the injection and ignition, and the distribution of flow velocity at ignition determine the distribution of the mixture concentration in the cylinder, which in turn affects the density of the flame surface and emissions. The delay ignition timing, the unburned methanol emissions increase significantly, while the nitrogen oxides emissions decrease rapidly. Optimal injection timing of 110°crank angle before top dead center and ignition timing of 21°crank angle before top dead center could obtain the best compromise of a medium compression ratio direct-injection twin-spark plug synchronous ignition methanol engine under steady-state lean-burn conditions. Thus, twin-spark plug synchronous ignition can ensure stable combustion and yield good performance with a medium compression ratio under lean-burn conditions. Highlights: Twin-spark plug synchronous ignition was proposed for methanol engine. Methanol late-injection strategy under medium compression ratio was used. Combustion of methanol engine at steady-state and lean-burn conditions was studied. Injection and ignition timings determined the distribution of mixture concentration. Optimal injection and ignition timings could obtain the best performance compromise.